2020
DOI: 10.1007/s11101-020-09710-8
|View full text |Cite
|
Sign up to set email alerts
|

Application of dietary supplements in the prevention of type 2 diabetes-related cardiovascular complications

Abstract: Type 2 diabetes, which accounts for the vast majority of diabetes worldwide is the result of a lowered sensitivity of the insulin receptors, resulting in impaired sugar metabolism is and chronic hyperglycaemia. There is no cure for type 2 diabetes, though some people with prediabetes and diabetes manage to reach and hold normal blood sugar levels, thus avoiding most of the complications that come with chronic hyperglycaemia; this is sometimes referred to as 'reversing diabetes'. A healthy diet, with sufficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 170 publications
(170 reference statements)
0
5
0
Order By: Relevance
“…Therefore, there is a great interest in developing a-glucosidase inhibitors, which, currently, are considered as first-line drugs for treating type-2 diabetes. Hussain et al (2020) reviewed aglucosidase inhibitors, reported in the last 40 years, isolated from fungi.…”
mentioning
confidence: 99%
“…Therefore, there is a great interest in developing a-glucosidase inhibitors, which, currently, are considered as first-line drugs for treating type-2 diabetes. Hussain et al (2020) reviewed aglucosidase inhibitors, reported in the last 40 years, isolated from fungi.…”
mentioning
confidence: 99%
“…Notably, flavonoids and carotenoids, natural phytochemicals commonly found in edible fruits and vegetables (F&V), have been shown to mediate immune-inflammatory responses and modulate non-cytokine mediators such as reactive oxygen species and nitric oxide (NO), thus potentially protecting against diabetes-related complications (24-27). A large body of research has focused on the preventive effects of flavonoids and carotenoids against the immediate effects of T2DM (28)(29)(30)(31)(32), but their protective effects against diabetic complications have remained less studied, with clinical evidence emerging but still limited (33,34). This review will primarily discuss the therapeutic potential of dietary flavonoids and carotenoids in preventing/treating diabetic complications based on in vivo evidence and examine the possible mechanistic bases involved with a particular focus on the immune-inflammation modulatory effects of those chemicals.…”
Section: Diabetes Managementmentioning
confidence: 99%
“…A potential benefit related to these outcomes has also been suggested for the intake of various dietary supplements (DS) in T2DM [for excellent reviews on their effects and mechanisms of action, see (6)(7)(8)]. These dietary supplements include, for example, vitamins such as vitamin C, folic acid or vitamin D (9)(10)(11), minerals such as chromium or zinc (12,13), dietary fiber (14), amino acids like L-arginine (15), complex fruit, vegetable-or plant extracts such as pomegranate, broccoli sprouts or tea extracts (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Given the benefits of regular physical exercise in T2DM patients (5) and the increasing interest in DS intake (6)(7)(8), the aim of this systematic review is to shed light on the effects of physical exercise programs combined with DS intake on health outcomes in T2DM patients, primarily on BMI, body fat mass, glycemic control, insulin sensitivity, the lipid profile, oxidative stress/antioxidative capacity and/or inflammatory markers/molecules. These variables may predict diabetes complications, adverse cardiovascular events and mortality (19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%